Modeling the Demand for Qualified Personnel in the IT Industry - E. V. Vasileva (Управление)
The author considers the problem of forecasting the demand for skills. The author’s model is a mathematical description of the movement of personnel potential of the University and of the employing organization in terms of continuous training of employees. The model describes the relationships between the structures of training, labour market, employers of University graduates. The University is viewed from two perspectives - as a staff software training and as an employer. The model is implemented in the simulation AnyLogic. The results of the scenario study the behavior of the system of reproduction of human capacity in the IT industry. As scenarios were chosen rapid, moderate growth and decline in the development of it industry, the aging workforce of the IT industry, decline in demand for the masters degree and the demand for judges from the it industry, demographic decline and growth.